Short communication: Identification of variation in the ovine prolactin gene of Chios sheep with a cost-effective sequence-based typing assay - Miltiadou, Despoina; Orford, Michael R.; Symeou, Simoni; Banos, Georgios (My University, 2017)
The present study identified single nucleotide polymorphisms (SNP) in the coding and untranslated regions of the ovine prolactin gene of Chios sheep. By developing a cost-effective direct sequence-based typing assay, around 600 bp of reliable sequencing data and clear identification of heterozygous positions was achieved. Five SNP were found, located in exons 2 (KC764410:g.567G>A, g.625C>T, g.683C>A) and 3 (KC764410:g.2015C>A, g.2101G>A), whereas the remaining exons were monomorphic. The identified SNP were synonymous, with the exception of the g.567G>A SNP, which results in an Arg to His amino acid change. As the sequencing cost of the sequence-based typing assay was 20 orders of magnitude lower compared with a standard Sanger method, the assay was also used as a genotyping tool. The identified polymorphism was genotyped for 247 ewes and was subsequently used in mixed model association analyses of milk yield, milk fat content, and litter size at birth. The association analysis revealed a significant dominance effect of 0.17 ± 0.07 of the g.2015C>A SNP on milk fat percentage, whereas a dominance effect of −21.33 ± 10.51 of the same SNP on total lactation milk yield was also estimated. The g.2015C>A SNP explained 2.47 and 3.68% of the total phenotypic variance of milk yield and milk fat percentage, respectively, whereas the corresponding values for the animal variance were 7.14 and 11.75%. A suggestive association of the nonsynonymous g.567G>A SNP with litter size at birth was also detected.
Keywords: SNP identification; Prolactin association; Sequence-based typing (SBT); Sheep